The The Influence of Instagram Social Media Marketing and Product Quality on Purchasing Decisions at Zaza Coffee in Pontianak - Yulanda, Risqi; Fachri, Helman (Dinasti Publisher, 2025)
The rapid growth of the coffee shop industry in Indonesia has driven business owners to adopt effective marketing strategies to maintain competitiveness. This study examines the impact of Instagram social media marketing and product quality on purchasing decisions at Zaza Coffee in Pontianak. Using an associative research approach, the study employs multiple linear regression analysis with data collected from 100 respondents who are customers of Zaza Coffee. The results indicate that social media marketing has a significant influence on purchasing decisions, with a beta coefficient of 0.388, while product quality also plays a significant role with a beta coefficient of 0.345. However, social media marketing exerts a more dominant effect on consumer purchasing behavior compared to product quality. The coefficient of determination (R²) of 0.446 suggests that 44.6% of purchasing decisions are explained by these two factors, while the remaining percentage is influenced by other variables. These findings highlight the importance of integrating digital marketing strategies with product quality improvements to attract and retain customers. By understanding the factors affecting purchasing decisions, business owners can optimize their marketing efforts and product quality to enhance customer satisfaction and strengthen their competitive advantage